MODIFIKASI MODUL DRIVER PADA LAMPU PRECISSION APPROACH LIGHTING SYSTEM (PALS) DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - Siti Azzahra Pasaribu; Muhammad Caesar Akbar (Jurnal Penelitian)
The runway is equipped with visual aids that provide the aircraft's direction and angle of inclination that must be followed for a safe landing, also served by the ILS (Instrument Landing System). The procedure for providing OJT service units at Sultan Syarif Kasim II Airport Pekanbaru is the Electrical Mechanical Facility (EMF) to support ongoing operational activities. Electrical Mechanical Facility (EMF) Units. is one of the work units of Sultan Syarif Kasim II Airport Pekanbaru which has the duties and responsibilities to operate, maintain and carry out repairs to all electrical and mechanical facilities equipment. Electrical facilities include AFL (Airfield Lighting), which is commonly used as a visual guide for pilots to take off and land an aircraft, and a generating system (Distribution Transmission). Mechanical Facilities include conveyors, escalators, travelators, lifts, plumbing systems, etc. This unit is located in the Main Power House (MPH) building.